English Language Learning Management At Pioneering International School (Rsbi) Sman I Salatiga - Muhammad Kristiawan (LINGUISTIKA, 2011)
The aim of this research is to describe English Language Learning Management at Pioneering International School (RSBI) SMAN 1 Salatiga in a frame of educationalPioneeringdecentralization.This research uses ethnography method. The ethnography method is natural approach, cultural character that uses inductive analysis, and the researcher as a key of instrument. The techniques of collecting data consist of interviewing, observation, documentation, and triangulation. The sources of information are headmaster, English teacher, students, and school committee. The technique which is used follows Miles and Hubermans concept. This technique consists of data reduction, data display, and making Conclusion.Results of this research are: (1) the planning of English learning is done by an English teacher and headmaster by the governmental support; (2) organizing of English learning consists of syllabus and lesson plan, teachers election and learning media; (3) the application of English learning is based on KTSPcurriculum and Cambridge; (4) the learning methods used are demonstrating and active learning; (5) evaluation consists of daily test, mid test, final test and national examination; (6) the purpose of English Teaming is based on KTSP curriculum and Cambridge; (7) the materials are taken from internet, Jakarta Post, Cambridge, and the book of senior high school; (8) there areten English teachers, one of them is native speak-eiâ¢ from United State (Bashi. V); (9) the minimum score is 75; (10) English teachers use media based on need and demand, such as TV, VCD, LCD, OFIP and language laboratory, (11) each room consists of forty students; (12) the classroom setting is still traditional and simple based on the material and topic taught; (13) the roles of teachers are fticifltatoi: motivator and innovator They also role as students parent and friend, (14) extracurricular club consists of English DaY (debate) and English Club; (15) the class control is done by the headmaster and the supervisor dirough daily test, mid test, final test an(] nationalexamination; (16) to upgrade the teachers professionalism, school uses questionnaire fromstudents and through conij.7arathlestudi%- (17) the participation of parent is high; and (18) theschool,, fee is from parent and government. The government hasnt fulfilled the all needs yet. Therefore, it needs support from parent.